A New Computerized Impedance Plethysmograph: Accuracy in the Detection of Proximal Deep-Vein Thrombosis in Symptomatic Outpatients - Prandoni, Paolo; Lensing, Anthonie W A; Huisman, Menno V; Jonker, Jan J C; Vigo, Mario; Borm, Judocus J J; Büller, Harry R; Sing, A K; Carta, Mariarosa; Cate, Jan Wouter ten (Thrombosis and Haemostasis, 1991)
Because of the lack of specificity of the clinical diagnosis it is appropriate in patients with clinically suspected deep-vein thrombosis to apply an objective test before starting anticoagulant treatment. Impedance plethysmography is a highly accurate technique for the detection of proximal-vein thrombosis with a reported sensitivity and specificity of 93 and 97%, respectively. In all previous reported evaluations of impedance plethysmography an apparatus which was developed in 1971 was used.A new computerized impedance plethysmograph, using a novel device to measure impedance, was blindly compared against venography in 443 consecutive outpatients with clinically suspected deep-vein thrombosis. In the first phase of the study the computerized impedance plethysmography test results of 242 symptomatic patients were used to develop a discriminant line. Subsequently, this discriminant line was validated in the second phase of the study in another 201 symptomatic patients. The combined sensitivity and specificity of these two phases for proximal-vein thrombosis was 91% [95% confidence interval (Cl), 86 to 94%] and 94% (95% CI, 90 to 96%), respectively, which compares favourably with impedance plethysmography.It is concluded that computerized impedance plethysmography is a simple, portable, non-invasive technique with a high accuracy for the detection of proximal vein thrombosis. However, before computerized impedance plethysmography can be used as the only test in the diagnosis of deep-vein thrombosis, the safety of withholding anticoagulant treatment to patients with repeated normal computerized test results should be assessed during longterm follow-up studies.